'New Normal' is a Name for a Fear and, Unfortunately, Roosevelt Was Right. Issue 79 (September 2015) - Shiller, Robert; Caginalp, Gunduz
<x xml:space="preserve">Abstract</x> Beacon of empiricism, nemesis of the efficient markets hypothesis, and Nobel Prize winner Robert Shiller speaks to Gunduz Caginalp about the new edition of Irrational Exuberance and the truth behind the 'new normal'